Profile of neurological disorders in a tertiary center of education in orthopedics - Celmir de Oliveira Vilaça; Fabio de Souza; Kelly Biancardini Gomes Barbato (Arquivos de Neuro-Psiquiatria)
Background Neurological conditions can cause secondary orthopedic disorders and can result from orthopedic surgical procedures. In addition, misdiagnosis and overtreatment involve both specialties. Epidemiological studies of neurological patients in tertiary units are often performed in emergency departments of general hospitals or rehabilitation centers. Objective Describe the clinical and epidemiologic profile of neurological disorders in a Brazilian federal tertiary center and education hospital in orthopedics in Rio de Janeiro. Methods We performed a retrospective study of the medical records of patients attended by neurology specialists of the internal medicine's department of the National Institute of Traumatology and Orthopedics from February 2014 to March 2020. Results We reviewed neurological referrals in the medical records of 1,349 patients in the period. The mean age of patients was 49.67 years (standard deviation [SD] ± 18.99). There was a predominance of females, corresponding to 751 (55.7%) patients. Regarding ethnicity, 684 (50.7%) participants were white, 550 (40.8%) non-white, and 115 (8.5%) non-classified. Peripheral neuropathies (34.1%), osteoarticular diseases (10%), epilepsy (8.3%), developmental disorders (7.9%), and neuromuscular diseases (7.3%) were the 5 groups with the largest numbers of cases. Conclusion The sample consisted mostly of females and white individuals, and approximately one third of the cases were of peripheral neuropathies. Epidemiological studies in neurology from tertiary centers of another medical specialty can improve the professional development of both specialties. This interdisciplinary approach can also optimize resources, help avoid misdiagnosis, and reduce disability.